A34 Understanding How the Built and Social Environment Shapes Willingness and Ability to Cycle in Later Life. Issue 2 (June 2015) - Jones, Heather; Chatterjee, Kiron
Abstract: Background: Being mobile by bicycle in later life has the potential to enhance wellbeing, not only through exercise, but as enabler of social interaction and connection to place and community. Changes in role and time use that accompany retirement afford the opportunity for patterns of mobility that are more localised and could be supported by cycling. However cycling activity amongst older age groups is much lower in the UK than Germany, Denmark and the Netherlands, suggesting a context that is less supportive of cycling in later life. Methods: Cycle Boom is a mixed methods project looking at how earlier contexts, roles and experiences, as well as contemporary urban environments, shape the willingness and engagement of those over 50 to cycle. Qualitative biographical interviews augmented with visual elicitation techniques were conducted with adults in this age category to elicit narratives of engagement with cycling through the life course. These were adults who varied in their current engagement in cycling from none to regular activity. Participants who still cycled took part in a videoed ride followed by an interview on their experience of negotiating the urban space by bicycle. In depth case summaries incorporating textual and visual elements were produced that detailed how individual's current spatial and temporal practice of cycling had developed in the context of life events, social contacts and physical environments. Analysis was comparative, visual and iterative and focused on common and distinct pathways of engagement with cycling through mid and later adulthood. Results: A range of health events including acute illness and loss of fitness and acuity of senses influenced older adults' ability and willingness to cycle both positively and negatively. Retirement was often a process during which the spatial and temporal patterns of cycling were redrawn. Whilst post-retirement cycling was often solitary social contacts and networks were often important sources of practical support or motivation for cycling. Different locations within the urban context seem to afford different opportunities and constraints for older adults to engage with cycling. Conclusions: We offer detailed studies of individual changes and continuities in cycling through the events and adjustments of mid and later life, and experiences of the velo-mobile, older citizen in urban environments. We propose policy goals to address some of the deterrents to cycling and returning to cycling that can affect older people and generally counter the tendency to overlook this population in the design and planning of cycling.